Sampling Statistics and Applications (Book). - Dugan, James E. (The Accounting Review, 1946)
Abstract Reviews the book "Sampling Statistics and Applications. Fundamentals of the Theory of Statistics," by James G. Smith and Acheson J. Duncan.